A systematic review of the safety of incretin-based therapies in type 2 diabetes. Issue 2 (3rd March 2016) - Evans, Marc; Bain, Stephen C.; Vora, Jiten
ABSTRACT: Introduction: Large randomized clinical trials have demonstrated that incretin-based therapies provide effective glycemic control in type 2 diabetes. Long-term safety assessments are ongoing. Methods: This systematic review of incretin-based therapy safety is based on 112 randomized clinical trials of duration ≥26 weeks published between January 2000 and February 2015 in patients with type 2 diabetes. Results: As expected, hypoglycemia rates were lower with dipeptidyl peptidase-4 inhibitors (DPP-4is) and glucagon-like peptide-1 receptor agonists (GLP-1 RAs) versus other oral antidiabetic drugs and insulin. The most common adverse events were infection and infestation (DPP-4is) and gastrointestinal (GLP-1 RAs). Pancreatitis cases were rare across all studies and, in the SAVOR-TIMI and EXAMINE trials, pancreatitis rates were similar in DPP-4i- and placebo-treated patients. No thyroid tumors were reported, and increased risk of cardiovascular events was not associated with DPP-4is in SAVOR-TIMI and EXAMINE, albeit over a short follow-up period. Conclusions : Overall, incretin-based therapies were well tolerated; however, their long-term safety profile should continue to be periodically assessed.